ANALISIS MONITORING SISTEM PEGAWAI MENGGUNAKAN METODE AGILE BERBASIS WEB DI KANTOR KEPALA DESA RAJEG - Yosafat Yusak Junior; Aditya, Eka; Ramadhan, Mardiko; Roeslan Djutalov (Journal of Research and Publication Innovation, 2023)
Personnel Information Systems have an important role in increasing the efficiency and effectiveness of employee data management in various institutions, agencies and companies. The transformation from a manual approach to a computerized system provides a significant change in the way work is done, enabling more efficient, precise and effective processes. The aim of this research is to develop a computerized personnel information system as a replacement for the manual system that is still used. By using this system, it is hoped that it will be able to improve the performance and efficiency of personnel operations through better, precise, fast and accurate storage, processing and management of employee data. The importance of facilities and infrastructure, including technology and information systems, is the key to improving work performance. Organizations are required to have competitiveness and excellence, which is achieved through understanding and adapting to changes in behavior and organizational structure. The use of technology and information systems is the basis for achieving excellence, involving effective interaction between thinking, processes, and the use of human resources and technology. This research seeks to design and implement a computerized personnel information system, which is expected to increase the effectiveness, efficiency and competitiveness of organizations in the era of information technology development.